2003
DOI: 10.1128/aem.69.4.2100-2109.2003
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Antibodies Do Not Affect the Composition of the Bacterial Microbiota in the Terminal Ileum of 10-Week-Old Mice

Abstract: Terminal restriction fragment length polymorphism (T-RFLP) analysis was conducted on the 16S rRNA genes of the bacterial communities colonizing the epithelial surfaces of the terminal ilea of open conventionally housed mice in an institutional small-animal facility. Polymeric-immunoglobulin-receptor-deficient (pIgR ؊/؊ ) mice that were unable to secrete antibodies across mucosal surfaces were cohoused with normal and otherwise genetically identical wild-type (C57BL/6) mice for 4 weeks. If secretory antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 50 publications
1
81
1
1
Order By: Relevance
“…Previous studies examining mouse mutants lacking secretory immunoglobulins have identified an altered microbial profile in the small intestine. [24][25][26] While these studies did now show an increase in Proteobacteria, the microbiota in the small and large intestine are known to be unique 38 and differences in the mouse models can alter the microbiota based on the presence or lack of IgM and IgG. Of note, there appears to be a reciprocal decrease in Bacteroidetes in mice that show an expansion of Proteobacteria, we can speculate that this is due to competition or inhibition by Proteobacteria, however the precise mechanism is unknown and is being investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining mouse mutants lacking secretory immunoglobulins have identified an altered microbial profile in the small intestine. [24][25][26] While these studies did now show an increase in Proteobacteria, the microbiota in the small and large intestine are known to be unique 38 and differences in the mouse models can alter the microbiota based on the presence or lack of IgM and IgG. Of note, there appears to be a reciprocal decrease in Bacteroidetes in mice that show an expansion of Proteobacteria, we can speculate that this is due to competition or inhibition by Proteobacteria, however the precise mechanism is unknown and is being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] In order to investigate if B-cells are involved in establishing the mature microbiota, we profiled the composition of major bacterial phyla in the colon of newborn and adult Ighm -/-deficient mice that have arrested B-cell differentiation. Lack of B-cells in adult mice resulted in an altered phenotype more consistent with the immature microbiota seen in neonatal WT mice characterized by expansion of Proteobacteria spp.…”
Section: Tlr and Myd88 Play A Limited Role In Regulation Of Intestinamentioning
confidence: 99%
“…Using this approach, we were able to assign a 69 % of the total fluorescence. However, if the threshold is set at 5 %, which served to remove any bias caused by the amount of PCR product while having a minor effect on the overall area of the remaining T-RFs (Sait et al 2003, Rees et al 2004), the TRFs assignation of this environmental sample goes up to 91.3 % of total fluorescence. Using these conditions the operational taxonomic units are less abundant, as clade II and clade HL, could not be included in the analysis.…”
Section: Picocyanobacteria Diversity In Natural Marine Watersmentioning
confidence: 99%
“…Specialisations of IgA as a mucosal Ig include basal-to-apical transport by epithelial cells (mediated by the polymeric Ig receptor), resistance to lumen proteolytic activity and binding to mucus (Johansen et al 2001). Functionally, IgA does not appear to directly influence the composition of the lumen commensal microflora (Sait et al 2003); however, it does act to prevent antigens and micro-organisms from penetrating the epithelium (Macpherson & Uhr, 2004b) and to pump antigens that have penetrated by binding before being transported into the intestinal lumen across epithelial cells (Brown et al 1984).…”
Section: The Mucosal Immune System Of Mammalsmentioning
confidence: 99%